The art of papercutting : 35 stylish projects for gifts, cards & decorations - Schneebeli-Morrell, Deborah (London : Cico, 2011)
Papercutting has a long history, originally as a traditional folk art practised across Europe and North America, and now elevated to new, sophisticated levels. Here, Deborah Schneebeli-Morrell presents a stunning collection of 35 papercutting projects, ranging from party decorations, decoupage pictures and paper flowers, to greetings cards and gift tags. All have easy-to-follow instructions, with advice on the best paper to use for a superb result.
Includes index.
Keywords: Paper work; Cut-out craft